Evaluation of the BCL-2, PI3K, PARP-1, and HSP90 pathways in breast, lung and glial cell lines for identification of candidate genes as therapeutic targets for overcoming radioresistance. - Manunu, Bayanika (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.